Grandparents raising grandchildren: support and resource-related issues - Jobe, John Andrew (Kansas State University, 2012)
Currently in the United States there are 2.7 million grandparent caregivers caring for 5.4 million grandchildren, with 883,386 of these grandparents caring for their grandchildren without any assistance from the child’s biological parent. These grandparents have unique needs and require support services that understand and recognize those needs. However, many of the resources currently available are not designed to assist this population. This report explores many of the issues grandparents face when taking over as the primary caregiver for their grandchild. Specifically this report highlights the financial, legal, and medical issues, as well as the need for respite care and housing. These particular issues were selected because they are commonly cited as difficult areas to navigate for grandparent caregivers, and also because there are crucial resources in each of these areas that allow grandparents to successfully raise their grandchild. Without these tools, the process of raising the grandchild can prove extremely difficult for grandparents, which can have negative consequences on the grandchildren. In addition it offers suggestions for grandparents seeking assistance regarding these issues, also providing several resources. This report also offers guidance for grandparent caregiver advocates and encourages future research and scholarship to explore programs assisting this population.
Keywords: Grandparents; Grandchildren; Kinship caregiver; Skipped generation household; Aging (0493); Early Childhood Education (0518); Ecology (0329); Gerontology (0351)